2009
DOI: 10.1017/s1479262108060930
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in varietal diversity of rice in Guinea

Abstract: Rice varietal diversity was assessed in Guinea on the basis of surveys of 1679 farms located in 79 villages of the four natural regions of the country. The descriptors used were the number of known varieties, the number of cultivated varieties and Shannon's diversity and evenness index.On the basis of their use rates, varieties were classified as major or minor types at the village scale and as regionally and/or nationally eminent varieties at these scales. Varietal diversity was high, especially in forest Gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The average number of varieties cultivated per village in the study area is low compared to that found in the villages of the island of Madagascar (10.9; Radanielina et al 2013), Guinea (24.6;Barry et al 2008), and in the Kumaun region of Indian Central Himalaya (11; Agnihotri and Palni 2007). However, the diversity maintained at the household level (2.2) is almost similar to that held by Malagasy (Radanielina et al 2013), and Indian farmers (Laishram et al 2020), but lower than those held by Nepalese farmers (Bajracharya et al 2010).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The average number of varieties cultivated per village in the study area is low compared to that found in the villages of the island of Madagascar (10.9; Radanielina et al 2013), Guinea (24.6;Barry et al 2008), and in the Kumaun region of Indian Central Himalaya (11; Agnihotri and Palni 2007). However, the diversity maintained at the household level (2.2) is almost similar to that held by Malagasy (Radanielina et al 2013), and Indian farmers (Laishram et al 2020), but lower than those held by Nepalese farmers (Bajracharya et al 2010).…”
Section: Discussionmentioning
confidence: 63%
“…Our results regrouped the rice accessions in 21 morphological groups based on seed characteristics. This diversity is very low compared to those found in Guinea (387 rice varieties; Barry et al 2008), in Bangladesh (670 unique rice varieties; Tiongco and Hossain 2015), and in Madagascar (346 rice varieties; Radanielina et al 2013). However, as in Lao (Appa Rao et al 2002), we noted that the same rice variety could be called by different names and different varieties could have the same name.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In our case, several facts argue against the hypothesis of replacement of the old rice landraces of long DTHD ( Og-1 and Osj-1 subpopulations) by new exogenous rice varieties of shorter DTHD ( Og-2 and Osj-2 subpopulations). (i) Penetration of improved O. sativa rice varieties, with shorter duration, in the slash- and-burn based upland rice cropping system of our study area was reported to be extremely limited (Barry et al, 2009) and no breeding program exists for the improvement and release of new O. glaberrima varieties. (ii) Distance based neighbour-joining tree did not show any structuring in relation with collect time.…”
Section: Discussionmentioning
confidence: 93%